Laryngeal ulceration in Behçet's disease: the role of centres of excellence in the UK. Issue 2 (8th February 2019) - Ghazal Asswad, Randa; Harrison, Anna; Hans, Paul S; Buzatu, Casandra
Abstract: Introduction: Behçet's disease (BD) is a rare complex multisystem inflammatory condition characterized by the triad of symptoms: aphthous ulcers of the mouth and genitalia and uveitis. Case report: We present the case of a 31-year-old Caucasian male who had a prolonged journey from first presentation until diagnosis of BD. For 11 years, he presented symptoms affecting the oral cavity and oropharynx, with worsening odynophagia and dysphagia and ultimately, development of stridor. Flexible laryngoscopy showed significant laryngopharyngeal ulceration and scarring. Treatment was with colchicine, corticosteroids and azathioprine and supervised by one of three newly established BD Centres of Excellence in the UK. Discussion: Although uncommon, ENT manifestations in patients with BD should be taken into consideration to allow for early recognition and treatment of what can become a life-threatening condition. In such situations, early referral to a BD Centre of Excellence is essential to provide confirmation of diagnosis and supervision of treatment.